Special operations: a hidden chapter in the histories of facial surgery and human enhancement. Issue 2 (6th July 2020) - Bailey, Roderick
Abstract : During the Second World War, Britain's Special Operations Executive (SOE), a secret service established to encourage resistance and carry out sabotage, employed various techniques of enhancing the ability of its personnel to operate undetected in enemy territory. One of these methods was surgery. Drawing on recently declassified records, this article illuminates SOE's reasons for commissioning this procedure, the needs and wants of those who received it, and the surgeons employed to carry it out. It also aims to underline the role of context in shaping perceptions of facial surgery, and the potential for surgery for wartime disguise to resonate with current debates about human enhancement.